Pengaruh Dukungan Sosial Orang Tua Terhadap Prestasi Belajar Siswa SMP Angkasa Halim Perdana Kusuma Jakarta Timur - Chientya Annisa Rahman Putrie; Muhammad Fauzia (Universitas Negeri Padang, 2019)
This study to determine the effect of parental social support on class VIII student achievement in social studies subjects at SMP Angkasa Halim Perdana Kusuma, East Jakarta.The research method used is to use an associative quantitative method. The techniques of taking sample using random sampling with a sample of 68 students in Angkasa Junior High School Halim Perdana Kusuma in East Jakarta. The data used is the regression correlation analysis. It’s can be seen from the calculation of simple ANOVA. Significant correlation coefficient tests were obtained from the model summary table.This means Ho is rejected. While the correlation coefficient of determination from the model summary table namely R square = 0.990 which means that 99 % of the variation in the social studies achievement variable is influenced by social support from parents. From analysis results is HO rejected. Thus